Understanding the Realities of Financial Crime in Public Institutions: Female Public Servants’ Insights - Awale, Abdirahman Abdinur; Abdullahi, Faduma Ahmed; Kulmie, Dayah Abdi (International Journal of Economics and Financial Issues, 2024)
This study assessed public female employees’ perceptions of financial crimes in Somali public sector, using a descriptive research. Research on financial crimes, corruption and fraud ware male dominated, so, female offenders, as well as female participation in research, have received less attention. However, recent studies have focused on the intersection of gender and financial crimes. Researchers collected primary data from 64 female employees working in various public organizations and analyzed it using SPSS. Studies based on perception play a key role in connecting actual circumstances with individual experiences. The results indicate that public female employees perceive financial crimes as widespread and complex issues, but also believe that they are both preventable and detectable. The findings of this study align with those of previous research, identifying the elements of the fraud triangle (Pressure, Rationalization, Opportunity) and fraud diamond (Capability) as the key contributors to financial crimes within the Somali public sector. The survey highlights the significant economic and social impacts of financial crimes, including increased government expenditures, budget deficits, impeded socio-economic development, and resource misallocation, as well as the detrimental effects on the private sector and public institutions. The paper suggests several measures to improve financial crime prevention. It recommends strengthening governance, accountability and transparency systems, establishing effective independent oversight bodies, increasing public access to financial information, promoting ethical culture and enforcing ethical codes for public servants, investing in law enforcement capacity, and educing socio-economic disparities to create a more equitable society. This study is the first attempt to assess public female employees’ perception of financial crimes in Somalia. It offers new perspectives on the root causes, and consequences of these bad practices, and sheds light on how these crimes can be prevented, and detected by offering key actionable insights to policymakers.